Rift Valley fever virus circulation in livestock and wildlife, and population dynamics of potential vectors, in northern KwaZulu-Natal, South Africa - Venter, Estelle Hildegard (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.